Angle of repose - Stegner, Wallace, 1909-1993. (New York, N.Y. : Penguin Books, 1992)
Stegner's Pulitzer Prize-winning novel is the story of four generations in the life of an American family. A wheelchair-bound retired historian embarks on a monumental quest: to come to know his grandparents, now long dead. The unfolding drama of the story of the American West sets the tone for Stegner's masterpiece. Four generations in the life of an American family are chronicled as retired historian Lyman Ward, confined to a wheelchair, decides to write his grandparent's history.
Grass Valley -- New Almaden -- Santa Cruz -- Leadville -- Michoacan -- On the bough -- The canyon -- The mesa -- The Zodiac Cottage.
Checked out to Lubec Memorial Library 01/05/2011 GH
"First published in the U.S.A. by Doubleday...1971" -- T.p. verso.
Winner of the Pulitzer Prize for Fiction for 1972.
Pulitzer Prize for Fiction, 1972.
Keywords: People with disabilities -- Fiction; Frontier and pioneer life -- West (U.S.) -- Fiction; Pioneers -- United States -- Fiction; Grandparents -- Fiction; Genealogy -- Fiction; Historians -- Fiction; Married people -- Fiction; Families -- Fiction; Older people -- Fiction; California -- Fiction; Domestic fiction